Aplicación de un recubrimiento a base de cáscara de piña (ananas comosus) y aceite esencial de semilla de aguacate (persea americana) para conservar queso fresco - Chamba Cumbicos, Lizbeth Tatiana (2019)
In Ecuador there is a large amount of agroindustrial waste that can be used for other purposes, for this reason experimental studies were carried out for the production of coatings with pineapple shells (Ananas comosus) and avocado seeds (Persea americana) in preservation of fresh cheese. Four treatments (Q2, Q3, Q4, Q5) were developed using coatings made from cassava starch and the flours of wastes, which were compared to a target (Q1). The quantification of 3 microorganisms was performed; (Aerobic mesophilic, Escherichia. Coli and Staphylococcus aureus) for 17 days, maximum cheese consumption time. Statistically for the UFC / g count, of the three pathogenic microorganisms there were no significant differences, none of the coatings retarded microbiological growth. The physical-chemical and mechanical tests of the coatings to be used were all statistically different, with the Q4 treatment having better characteristics. In the Q2 and Q4 organoleptic tests, they were the most pleasant because it helped to maintain the characteristics of the fresh cheese while the Q5 treatment the smell and taste was very unpleasant due to the characteristics of the avocado seed (Persea americana).